Analisis Peran Pemerintahan Dalam Pengendalian Pertumbuhan Penduduk - Diana watik; Anita Trisiana; Farida novitasari (Universitas Slamet Riyadi, 2022)
A collection of people to have in an area or a person entitled to occupy an area or country on the condition that the person must have official letters to people living in the area are called. Demographic studies should be understood to learn about population in the area. Writings on demographic is sort of the population, distribution, and the composition of population. As well as from time to time the change third factor. For the number of Indonesia largest population in fourth place in the world, with a population of as many as there are 237,6 million people. The larger the population and will bring challenges such as improve the citizens welfare, develop job opportunities, reducing poverty, to develop the quality of education and health, add infrastructure, and community service. In the process reduce the population growth rate introduced steps have been planned before.